Analysis of Safety Metrics Supporting Air Traffic Management Risk Models - Angela Errico; Lidia Travascio; Angela Vozella (Engineering Proceedings, 2025)
This paper provides a study on safety metrics that are used to describe the airspace and identified as important factors influencing and characterizing the safety in airspace considering the traffic of aircraft in different flight phases. Different capabilities, frequently monitored, support the safety warning systems for the airspace, where precursory metrics within the barrier model presented by EUROCONTROL indicate the stages in the evolution of a possible barrier violation, triggering actions by Air Traffic Control and collaborative decision-making when airspace is degrading in terms of safety. The identified metrics have been analyzed, taking into account the overall scenario of aircraft evolution in an air traffic sector related to the intrinsic characteristics of airspace. A case study is presented related to separation minima infringements, and it addresses safety metrics based on the different tactic geometries in en-route ATM.